Study of Organizational climatic factor for employee effectiveness: A Study of Jalandhar Leather factories (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Every organizational activity is oriented around a set of variables which together constitute a climate of work. Climate is the atmosphere in which individual help, reward, judge, constraint & perceive about each other. It influences the morale & attitude of individual towards his work & his environment. It can also be said that climate designates the quality of co-operation, the extent of members dedication or commitment to organizational purpose & the efficiency with which the purpose becomes translated into results. This study aimed at studying the important climatic factors which helps in increasing employee effectiveness. And to study the influence of these factors on employee effectiveness.